Labours’ productivity in the construction site - Rad, Kiyanoosh Golchin (2014)
Productivity of workers is important to enhance the completion of the project within the required time and quality. Majority of the project elements and activities are based on labour performance. Construction activities are recognized as labour-intensive as it rely more on human efforts. Contractors have duties to handle the work in it best way for increasing the quality and decreasing time and also cost. Frequently, at construction sites it is observed that contractors do not pay attention to the productivity of workers and its effect on the overall productivity. Usually they do not measure labour productivity in the construction projects and also they cannot compare productivity rates in the construction sites. The aim of this study is to assess the factors that influence the workers’ productivity and the relationship between workers’ productivity and job satisfaction. The objectives of the study are to assess the level of understanding of contractors regarding the workers’ productivity in construction industry, to assess the level of implementation of contractors to improve workers’ productivity in construction site, to evaluate the main factors that influence the workers’ productivity in construction industry and to identify the relationship between job satisfaction and workers’ productivity. The data is collected through questionnaires and interviews. A total of 85 questionnaires were distributed to the respondents and 53 questionnaires were received duly answered. The data is analysed using Average Index and SPSS. From the study, the level of understanding of contractors regarding the workers’ productivity in construction industry is “Understand”. The contractors understand the impact of productivity on cost, time and quality. The steps taken by the contractors to improve workers’ productivity in construction site are monitoring labour activities, improving working conditions and training experienced labour. The main factors that influence the workers’ productivity in construction industry are lack of required material, lack of required tools, poor access, weather conditions, construction accidents, control delays and quality of required work. There is a significant correlation between job satisfaction and also productivity rate of the construction workers. In other word by increasing the job satisfaction their productivity would be enhanced and vice versa.